Making Crusades. The importance of crusades for Europe - Boborahimov Shoxruhbek; Axtamova Xurshida; Toshboyeva Farangiz; Rahmonqulov Ma'murbek (Zien Journals, 2022)
The reasons for the crusades in which the crusades participated in these marches, leaders, managers of the crusades, were highlighted by issues such as the importance of managers, cruscriptions, the importance of crusades for Europe
Keywords: Cruses; Maniksert; Alexei; Urban LL